Review: Effect of probiotics on gastrointestinal function: evidence from animal models - Elena F. Verdú; Premysl Bercik; Stephen M. Collins (Therapeutic Advances in Gastroenterology, 2009)
The digestive tract works through a complex net of integrative functions. At the level of the gut, this integration occurs between the immune, neuromotor and endocrine systems, the intestinal barrier and gut luminal contents. Gastrointestinal function is controlled and coordinated by the central nervous system to ensure effective motility, secretion, absorption and mucosal immunity. Thus, it is clear that the gut keeps a tightly regulated equilibrium between luminal stimuli, epithelium, immunity and neurotransmission in order to maintain homeostasis. It follows that perturbations of any of these systems may lead to gut dysfunction. While we acknowledge that the gut—brain axis is crucial in determining coordinated gut function, in this review we will focus on peripheral mechanisms that influence gastrointestinal physiology and pathophysiology. We will discuss the general hypothesis that the intestinal content is crucial in determining what we consider normal gastrointestinal physiology, and consequently that alteration in luminal content by dietary, antibiotic or probiotic manipulation can result in changes in gut function. This article focuses on lessons learned from animal models of gut dysfunction.